O Sistema de Seleção Unificada e a escolha pelas licenciaturas na Universidade Federal de Viçosa - Thainara Cristina de Castro Ariovaldo (2018)
The general objective of this research was to investigate how the Unified Selection System (Sisu) interfered in the choice of higher courses at the Federal University of Viçosa (UFV), examining undergraduate degrees that had the highest increase in the ratio of candidate per vacancy after the implementation of this new mechanism of selection. Taking the references from the Sociology of Higher Education, the hypothesis was that the increase of the demand for these courses was related to the way of how Sisu works, by stimulating strategic attitudes by the candidates in choosing the courses. By providing more up-to-date information about the score notes, this model would encourage the choice of courses or institutions that, while not matching the candidates actual preferences, would have a better chance of being approved according to his performance at Enem. In order to investigate this hypothesis, we delimited two methodological strategies: the first one is related to the analysis of institutional data about students enrolled in 2010, one year before the implementation of Sisu in the institution, and in 2015, when the students that used Sisu had already studied the first two years of the courses, period when the data was collected; the second strategy refers to the analysis of data collected through the application of questionnaires to students who enrolled in the degree programs where there was an increase in the demand for places after the adoption of Sisu. The institutional data allowed us to verify the changes occurred in the demand for all the courses, and in the percentages of dropout as well. This information strengthened the hypothesis as we observed that the courses that had the highest increase in the ratio of candidates per vacancy are precisely the most accessible ones, with lower scores, but they are also courses with highest dropout rates. This relationship between initial strategic choice and evasion became clearer with the data that came from the questionnaire indicating that students who evaded or intended to evade made their course choices early on and modified their preferences according to the grade obtained on Enem. Thus, the data indicate the influence of Sisu in the increase of degrees demand in the UFV, being the result of strategic and pragmatic choices of access, which are followed in many cases by dropout. The results obtained reinforce the findings of the Sociology of Education that social inequalities continue to guide the choices of higher education. Even though the Sisu game seems to offer equal opportunities for all, family and school characteristics limit or expand the way students play.